A cross-sectional study on social competence in children with speech sound disorders after cleft palate operation and functional speech sound disorders - LIN Sifan, MA Siwei, HUANG Qi, YANG Feng, LIANG Zhigang (Kouqiang yixue)
Objective To find out the social competence level of school-age children with speech sound disorders after cleft palate operation and functional speech sound disorders. Methods Thirty-four school-age children with postoperative cleft palate speech sound disorders and thirty-seven school-age children with functional speech sound disorders attending a specialty clinic for the diagnosis and treatment of childhood speech and language disorders in 2023 were selected, and 32 age- and gender-matched normal children in a local elementary school were also randomly selected as the normal group. The Achenbach Child Behavior Checklist was used to assess the social competence of the three groups of children and a cross-sectional study was conducted. Results Children with cleft palate speech sound disorders and functional speech sound disorders had lower scores on activity, communication and academic ability, with specific manifestations varying in different gender groups, but there was no significant difference in scores between the two groups. In contrast, the activity and communication scores of the functional speech sound disordergroup were significantly lower than those of the normal group(P<0.05). Conclusion School-age children with cleft palate speech sound disorders and functional speech sound disorders are at a higher risk of difficulties in social functioning, in terms of activity, communication and academic ability, whereas speech sound disorders may be one of the most important influencing factors of such difficulties and cleft palate does not have an additional impact on the social competence level of the child.